Desentralisasi Fiskal Daerah Otonom Baru; Studi Analisis Kemampuan Keuangan Pada Kebupaten/Kota di Provinsi Kepulauan Riau Sebagai Daerah Otonom Baru - Amalia, Shafiera (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
This research aims to describe fiscal independency in regions (cities) /municipalities in Kepulauan Riau Province. Researcher selected Kepulauan Riau Province because seven regions/municipalities in Kepulauan Riau Province are new local government; and regions/municipalities in Kepulauan Riau Province have a lot of natural resources. Fiscal independency is measured used degree of Fiscal Desentralization concept. This Research used qualitative approach and descriptive method.Beside that, this research used data local government budget (APBD) regions/municipalities in Kepulauan Riau Province periode 2008-2012 which is got from Indonesian Finance Ministry. The result shows there are five regions/municipalities in Kepulauan Riau Province have well fiscal independency and low dependency about central government. And just two regions/municipalities in Kepulauan Riau Province still have bad fiscal independency and high dependency about central government.